2020
DOI: 10.1016/j.dsx.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown in COVID 19 on glycemic control in patients with type 1 Diabetes Mellitus

Abstract: Background and aims COVID 19 is a novel pandemic affecting globally. Although no reliable data suggests that patients of well controlled Type 1 Diabetes Mellitus (T1DM) being at increased risk of becoming severely ill with SARS-CoV2, but lockdown may impact patients with T1DM requiring regular medications and follow up. Hence this study was planned to see the impact of lockdown on glycemic control in patients with T1DM. Methods A cross sectional study was done in T1DM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
197
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(217 citation statements)
references
References 23 publications
11
197
5
4
Order By: Relevance
“…Our data mainly consisted of people having type-2 diabetes (87.01%). Recent literature has mainly focused on disrupted glycemic control among type-1 diabetes people [ 19 , 21 ]. Therefore, irrespective of the type of diabetes, there is a need to monitor BGLs in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data mainly consisted of people having type-2 diabetes (87.01%). Recent literature has mainly focused on disrupted glycemic control among type-1 diabetes people [ 19 , 21 ]. Therefore, irrespective of the type of diabetes, there is a need to monitor BGLs in this population.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only a few papers have discussed the association between the COVID-19 outbreak and its impact on diabetes care in India. However, these studies had a relatively smaller sample size and were primarily conducted during the period of nation-wide lockdown [ [18] , [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in 143 patients with diabetes in Central India, 39% patients reported worsening of hyperglycemia [ 16 ]. A small study on 52 patients with type 1 diabetes in north India showed a statistically significant increase in average blood glucose and HbA1c during lockdown [ 17 ]. This is in contrast to the findings of improved glycemic control and reduced glycemic variability in studies in type 1 diabetes done in Spain, Italy and United Kingdom [ [18] , [19] , [20] ].…”
Section: Effect Of Nationwide Lockdown During Covid19 Pandemicmentioning
confidence: 99%
“…4 health, children's education, behaviours relevant to chronic disease, as well as severe social and financial consequences. [6][7][8][9][10] There is an urgent need to understand how control measures can be further strengthened in South Asia, both to reduce the high rates of ongoing transmission, and to mitigate their unintended adverse consequences.…”
Section: Introductionmentioning
confidence: 99%